2019
DOI: 10.1016/j.uclim.2019.100490
|View full text |Cite
|
Sign up to set email alerts
|

Defining scales of the land use effect to map the urban heat island in a mid-size European city: Rennes (France)

Abstract: The Urban Heat Island (UHI) is a climatic phenomenon linked to urbanization. In the context of climate change, municipalities have to adapt the city to increase in heat waves by managing the UHI. This study aims to map the UHI of a mid-size city (Rennes, France) and to define the relevant land use factors. The UHI was measured by 22 weather stations in different contexts: urban, suburban and periurban. After investigating the UHI weather conditions, we used a multi-criteria method by linear regression to build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 56 publications
3
28
0
9
Order By: Relevance
“…On the other hand, the buffer size for the bare-soil surfaces was between 50 m and 1000 m depending on the indicator (respectively density of bare-soil and BI, and NDBaI, and Enhanced Built-Up and Bareness Index (EBBI)). In this latter case, this size is similar to that of previous studies [46].…”
Section: Implication Of Important Predictors In Urban Air Temperaturesupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the buffer size for the bare-soil surfaces was between 50 m and 1000 m depending on the indicator (respectively density of bare-soil and BI, and NDBaI, and Enhanced Built-Up and Bareness Index (EBBI)). In this latter case, this size is similar to that of previous studies [46].…”
Section: Implication Of Important Predictors In Urban Air Temperaturesupporting
confidence: 91%
“…However, in this study, it was found that the buffers with the best correlation between air temperature and building density, based on LiDAR data, were 5 and 10 m. Furthermore, the vegetation density obtained from LiDAR, which explains air temperature in an optimum way, was within a radius of 50 to 200 m, regardless of its height (low, medium, or high; Figure 5). This also corresponds to a smaller buffer size than that used in previous studies [46]. On the other hand, the buffer size for the bare-soil surfaces was between 50 m and 1000 m depending on the indicator (respectively density of bare-soil and BI, and NDBaI, and Enhanced Built-Up and Bareness Index (EBBI)).…”
Section: Implication Of Important Predictors In Urban Air Temperaturementioning
confidence: 72%
“…In addition, it is forecast that by 2050 Lyon will have the climate of Canberra (Australia), with an increase in annual temperatures of 1.8 • C compared to the reference period 1971-2000 [66]. The number of summer days, which is defined according to the ETCCDI indices as days with maximum temperatures above 25 • C [67,68], tends to increase over the same period. The number of heat waves has increased sharply since the decade 1994-2003 [23].…”
Section: Study Area: the Metropolis Of The Greater Lyon Areamentioning
confidence: 99%
“…En outre, il est nécessaire d'estimer au mieux la température de l'air en tous lieux, notamment face à la rationalisation actuelle du réseau de stations météorologiques fixes de Météo France (Journal officiel du Sénat, 2012). En France, les agglomérations qui disposent de leur propre réseau de stations météorologiques fixes ne sont que peu nombreuses, comme à Rennes ou à Dijon (Foissard et al, 2019 ;Richard et al, 2018).…”
Section: Introductionunclassified